PHYSIOLOGICAL, ENZYMATIC AND SANITARY QUALITY OF WHEAT SEEDS TREATED WITH ZINC SULFATE DURING STORAGE - Tunes, Lilian; Lemes, Elisa; Almeida, AndrÃ©ia; Gadotti, Gizele; Fonseca, Daniel; Muniz, Marlove (REVISTA DE AGRICULTURA, 2015)
The objective of this study was to evaluate the effect of wheat seed coated with zinc, through enzymatic and health aspects during storage. It was concluded that wheat seed coating with zinc at doses of 3 mL to 4 mL ZnSO4 support in maximum expression of physiological quality, in addition to wheat seed coating with zinc sulfate is effective during period of six months of storage. There are variations in expression pattern of EST and GOT between wheat seeds and seedlings, in different doses of zinc sulfate during storage. Zinc supplied via seeds, associated with fungicide and polymer, results in a lower incidence of fungi in seeds throughout storage period.